Oikumene Sebagai Pondasi Persatuan Umat - Selviana Putri Naibaho; Meditatio Situmorang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
In the Christian context, ecumenism refers to a movement that unites various denominations separated by doctrine and tradition. The qikumene movement is the cornerstone of Christian unity across denominations with the aim of creating unity in diversity. This study investigates, through a qualitive approach, the role of oikumene in strengthening inter-reilious relationsships important for maintaining the harmony of society’s diversity. The reason for this writing is the importance of understanding the role of oikumene in creating religious harmony the word oikumene comes from the greek word meaning “one house” it aims to unite diverse Christians churches based on doctrine and tradition. The conclusions of this document emphasizes that ecumenism can be a reason to create harmonious unity within the church and at the same time a reason to create peace between Christians and communities. The result show the importence of this movement in strengthening inter-chriatian realations and contributing to social harmony.